2004
DOI: 10.1136/bmj.328.7449.1162
|View full text |Cite
|
Sign up to set email alerts
|

Doctors' experience with handheld computers in clinical practice: qualitative study

Abstract: Objective To examine doctors' perspectives about their experiences with handheld computers in clinical practice. Design Qualitative study of eight focus groups consisting of doctors with diverse training and practice patterns. Setting Six practice settings across the United States and two additional focus group sessions held at a national meeting of general internists. Participants 54 doctors who did or did not use handheld computers. Results Doctors who used handheld computers in clinical practice seemed gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
119
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(126 citation statements)
references
References 7 publications
(5 reference statements)
5
119
2
Order By: Relevance
“…Provision of smartphones uploaded with clinical decision support software (CDSS) to medical students was associated with increased use in clinical settings and improved knowledge of evidence-based medicine 20 . Resident Doctors who shoulder greater responsibility in patient care consider smartphones an important tool in enhancing productivity, quality of patient care and services 21 .…”
Section: Original Articlementioning
confidence: 99%
“…Provision of smartphones uploaded with clinical decision support software (CDSS) to medical students was associated with increased use in clinical settings and improved knowledge of evidence-based medicine 20 . Resident Doctors who shoulder greater responsibility in patient care consider smartphones an important tool in enhancing productivity, quality of patient care and services 21 .…”
Section: Original Articlementioning
confidence: 99%
“…PDAs have been in use by doctors for several years (McAlearney et al, 2004;McLeod et al, 2003), but until now there has been no data on PDA use in UK medical students. Using an online questionnaire of all undergraduate medical students in one UK medical school, we undertook an evaluation of PDA usefulness and uptake.…”
Section: Dear Sirmentioning
confidence: 99%
“…The PDA in particular has great potential for use among nurses for prescribing and recording clinical data on home visits, and a recent qualitative study has confirmed that, in the United States at least, there is growing enthusiasm for the use of handheld computers in clinical practice. 15 The potential of the use of this technology by professionals involved in communitybased health care -home visits, chronic illness reviews and palliative care, for example -is enormous, and deserves more research attention.…”
mentioning
confidence: 99%
“…This means achieving an understanding of the barriers to the uptake of information technology in healthcare systems, and the means of overcoming them, as a matter of urgency; research of the kind published by McAlearney and colleagues is capable of illuminating professional attitudes in a way that can form the basis for training and educational interventions. 15 The impact of the hardware in intimate healthcare settings and patients' views about computer use, and also about data storage and security, are becoming increasingly important, as is the need to provide evidence, from trials whenever possible, on the benefits in terms of health outcomes of engagement with current and future health-related technologies. All information contained in this survey will be treated in the strictest of confidence.…”
mentioning
confidence: 99%